2021
DOI: 10.1007/s13201-020-01343-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of powdered and granular activated carbon from Palmae biomass for mercury removal

Abstract: Two forms of activated carbon (i.e., granular and powdered forms) used to test mercury removal in solution. These activated carbons were obtained from the shells of a palmae biomass and used in mercury ion removal in aquatic systems. The African palmae shell taken out from a broadly and simply full-fledged palm tree. This biomass serves as a precursor in the formulation of activated carbons not documented. The powdered and granular fractions of activated carbons described for chemical composition, isoelectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 34 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Biomass-based activated carbon materials were also used for the fixation of gaseous Hg 0 (Skodras et al 2007 ; Asasian et al 2012 ; Egirani et al 2021 ). Liu et al reported the valorization of seaweed biomass into activated carbon for the adsorption of Hg 0 in the air (Liu et al 2019a , b ).…”
Section: Adsorption Of Pollutants In Air Phasementioning
confidence: 99%
“…Biomass-based activated carbon materials were also used for the fixation of gaseous Hg 0 (Skodras et al 2007 ; Asasian et al 2012 ; Egirani et al 2021 ). Liu et al reported the valorization of seaweed biomass into activated carbon for the adsorption of Hg 0 in the air (Liu et al 2019a , b ).…”
Section: Adsorption Of Pollutants In Air Phasementioning
confidence: 99%
“…Adsorption is one of the widely used and easily implementable technology known for its efficiency in removing organic pollutants and various metal ions [5]. Although commercial activated carbon is the most commonly used adsorbent due to its high adsorption capacity [6], its usage is limited due to its high cost and difficulty in regeneration, particularly for the treatment of large volumes of polluted effluents [5]. Therefore, recent research has focused on exploring alternative adsorbents that are costeffective, environmentally friendly, and preferably sourced from local waste or natural substances [7].…”
Section: Introductionmentioning
confidence: 99%
“…[12]. Numerous papers have been published on the elimination of Hg(II) via various sources, namely molecularly imprinted polymers (MIPs) [13,14], graphene oxide [15,16], activated carbon [17][18][19][20][21], carbon nanotubes [22], biochar [23,24], magnetic materials [25], metals, and metal oxides [26]. Another water treatment technique that is commonly used for Hg(II) removal is adsorption, and this has become a more important technique due to its efficacy, ease, low cost, and practicality at low concentrations.…”
Section: Introductionmentioning
confidence: 99%